Risk Factors and Clinical Manifestations in Hyperthyroidism: Case Report: Risk Factors and Clinical Manifestations in Hyperthyroidism - Anidha, Yusrita; Ayu, Wilis Cahyaning; Sari, Nur Mufida Wulan; Nadhiroh, Siti Rahayu (Universitas Airlangga, 2023)
Background: The recommended iodine intake for adult women is 150-300µg and for men <150µg, which functions in maintaining normal thyroid function. Hyperthyroid condition is characterized as increased synthesis or secretion of hormones by the thyroid gland. A family history of Graves' disease is the most frequently found risk factor, namely 60-80% worldwide. The prevalence of hyperthyroidism cases in Indonesia is around 6.8% Objectives: Comprehensively identifying risk factors and clinical manifestations of hyperthyroidism in case studies. Methods: This research was carried out with a systematic review using two databases, namely Pubmed and Scopus. The literature search strategy was carried out using Convidence software by including predetermined inclusion and exclusion criteria. There were 11 selected pieces of literature published from January 2016 to October 2022 Discussion: A total of 11 case studies showed that women dominated cases of hyperthyroidism with a ratio of 3:1. Through a systematic review conducted by researchers, it shows that Graves' disease is the leading risk factor and clinical manifestations such as swelling of the thyroid gland, difficulty breathing, progressive weight gain, tremors, and heart palpitations are often found. Conclusion: Patients who are female and have a family history of Graves' disease are the most common risk factors found with clinical manifestations of swollen thyroid gland, difficulty breathing, progressive weight gain, tremors, and palpitations.